2016
DOI: 10.36834/cmej.36644
|View full text |Cite
|
Sign up to set email alerts
|

Curricular initiatives that enhance student knowledge and perceptions of sexual and gender minority groups: a critical interpretive synthesis

Abstract: Background: There is no accepted best practice for optimizing tertiary student knowledge, perceptions, and skills to care for sexual and gender diverse groups. The objective of this research was to synthesize the relevant literature regarding effective curricular initiatives designed to enhance tertiary level student knowledge, perceptions, and skills to care for sexual and gender diverse populations.Methods: A modified Critical Interpretive Synthesis using a systematic search strategy was conducted in 2015. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Structural setbacks to intervention assessments included that as many as a half were optional (resulting in potential for selection bias), response bias, short-term nature of assessments, and lack of research that evaluates the comparability of scales used in different intervention assessments. 46 , 47 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural setbacks to intervention assessments included that as many as a half were optional (resulting in potential for selection bias), response bias, short-term nature of assessments, and lack of research that evaluates the comparability of scales used in different intervention assessments. 46 , 47 …”
Section: Resultsmentioning
confidence: 99%
“…A truly effective pedagogical intervention has been described as one that teaches transgender health in a way that does not create a narrative of a medicalized or pathologized “other” but rather encourages evaluation of the structural and cultural causes of gender minority health inequities. 47 Other structural changes in pedagogic delivery would benefit transgender medical education. The literature contains an emerging consensus that modular, ie, one time or discrete, interventions are strongly associated with short-term improvements in attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent scoping review of improving medical students' and residents' training and awareness of TGD health care found that consensus is lacking on exactly which educational interventions to use to address this topic [92]. Another review focusing on curricular initiatives that enhance student knowledge and perceptions of sexual and gender minority groups concluded that "multi-modal approaches that encouraged awareness of one's lens and privilege in conjunction with facilitated communication seemed the most effective" [93]. The literature supports a shift toward longitudinally integrated and clinical skills based pedagogical interventions [92].…”
Section: What Educational Interventions Have Been Described?mentioning
confidence: 99%
“…Two reviews focused on ability to care for sexual and gender minority people, and one review focused solely on transgender and gender-diverse people. 47 , 61 , 62 Educational interventions studied included lectures, online modules, panels with sexual and gender minority people speaking about their lived experiences, and encounters with transgender and gender-diverse standardized patients. Overall, the authors noted that while all studied interventions seemed to improve knowledge, confidence or attitudes in post-intervention testing, these findings were limited by the one-time nature of the intervention and the short follow-up time of the post-test.…”
Section: Transgender Health In Medical Educationmentioning
confidence: 99%